Development of new steam methane reforming mobile plant with micro-scale catalytic channels - Madon, Rais Hanizam (2019)
The search for clean alternative energy sources is vital to feed the ever-increasing world energy consumption. It is widely accepted that hydrogen is the cleanest and abundant energy source of the future. Currently, more than 90% of world hydrogen production is made via catalytic steam methane reforming (SMR). A performing catalyst favors thermodynamic equilibrium that ensures good hydrogen selectivity. This research explores the potential of SMR yield intensification using experimental micro reactor and active noble metal catalyst (Rhodium aluminide and Ruthenium aluminide). For that purpose, a laboratory scale SMR test rig bench was designed, fabricated and developed. A new micro channel reactor with interchangeable catalyst modules for methane conversion process was set up and tested. The rig is able to provide evaluation of SMR experimental tests, such as catalyst performance, conversion rate and products at output stream, with controlled reactants steam to carbon ratio up to 5:1 and reaction temperature up to 700°C. The developed conventional and noble metal catalyst for this research, affirmed and proved that the combination of test rig bench and micro reactor managed to generate methane conversion according to the theory related to material catalyst. From this work, reaction temperature 650°C and steam to carbon ratio of 3:1 were found to yield the optimum methane conversion and hydrogen formation for the developed catalyst. Using such setup, the use of noble metal catalyst was able to reform methane to hydrogen within 1 minute from the start of reaction as compared to 60 minutes using conventional catalyst. It was found that the rate of reaction (methane disappearing rate) of –r´CH4 (mol CH4 / g catalyst.s), for Rhodium aluminide yield the highest of 181.58, followed by Ruthenium aluminide with 154.39 and lastly Nickel aluminide of 1.32. The outcomes of this work has the potential to be scaled up for hydrogen production supply chain system of future fuel-cell electric vehicle transportation sector especially in any region with affordable natural gas price.